Dessecação pré colheita de trigo (Triticum aestivum) com a aplicação de Paraquat e Glufosinato: componentes de rendimento e produtividade - Lago, Eduardo (2019)
The wheat is a crop that occupies the largest area planted among winter cereals in the southern Brazilian region. Production factors such as climate are very influential in crop productivity, forcing some farmers to use desiccants to produce a uniform crop with better humidity conditions and harvest anticipation. The desiccation management should be carried out in an appropriate way to make the most of the crop's productivity and production factors. This work aims to analyze the previous and late desiccation on wheat with two different treatment products. The experiment was carried out in the field at the Universidade Tecnológica Federal do Paraná, Campus Dois Vizinhos, where wheat plants were grown in the field from which they were desiccated with paraquat and glufosinate ammonium at stages 77 to 83 and stage 85 following the Zadoks scale (1974). the analyzed variables were the number of normal and failed grain in 10 ears, pH and grain moisture, a thousand grain mass and productivity. Two control treatments were also used for this experiment. The data submitted to the Scott-knott test did not present statistical difference for the variables PH, Humidity, Mass of a thousand grains and productivity, for the variables of normal grains and failed grains, it was observed that the treatments in the stages 77 to 83 present a higher incidence of failed grains whereas stage 85 desiccation only the application of glufosinate was statistically equal to the controls.